Pengaruh Media Poster Commnet Untuk Meningkatkan Cara Berfikir Kritis Siswa Pada Mata Pelajaran PPKn Kelas V SDN 112 Pekanbaru - Ningsih, Warna; Laili Rahmi (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
This study aims to determine whether there is an influence of poster comment media in increasing students' critical thinking in the Civics Subject of Class V Students at SDN 112 Pekanbaru. This type of research is quantitative research using a pre-experimental approach. The population and sample of this study are Grade V B students at SDN 112 Pekanbaru totaling 35 students. Data collection techniques using tests, observation, documentation. This test uses validation and reliability. For analysis prerequisite test namely normality test, homogeneity test, hypothesis test. While testing this hypothesis using the T test results in a significant value of less than 0.05, namely Sig. (0.000) < 0.05 so that Ho is rejected, and Ha is accepted. The decision to test the hypothesis partially can be concluded that there is an influence of poster comment media on students' critical thinking in Civics learning.